Antidiabetic screening of some Indonesian marine cyanobacteria collection - SRI PRIATNI; THELMA A. BUDIWATI; DIAH RATNANINGRUM; WAWAN KOSASIH; RINA ANDRYANI; HANI SUSANTI; DWI SUSILANINGSIH (Society for Indonesian Biodiversity, 2016)
Priatni S, Budiwati TA, Ratnaningrum D, Kosasih W, Andryani R, Susanti H, Susilaningsih D. 2016. Antidiabetic screening of some Indonesian marine cyanobacteria collection. Biodiversitas 17: 642-646. Cyanobacteria have been known as a potential extracellular-polysaccharide (EPS) producer. The objective of this study was to screen the marine cyanobacteria as potential antidiabetic agents. The present investigation was designed to determine the antidiabetic activity of EPS, intracellular-polysaccharide (IPS) and biomass extracts from marine cyanobacteria isolates. 10 cyanobacteria isolates were cultivated in IMK medium, at 25oC for 21 days. The morphology of cells was identified by a light microscope. EPS and IPS were separated by ethanol precipitation method and their antidiabetic activity was analyzed by the inhibition of Î±-glucosidase activity method. Results of morphology identification of 10 cyanobacteria isolates consist of Oscillatoria limnetica, Oscillatoria sp., Leptolyngbya sp., Pseudanabaena sp., Lyngbya sp. and Phormidium sp., Coelastrella sp., Aphanothece sp. and Synechococcus sp., and Chroococcus sp. Almost all of EPS from marine cyanobacteria isolates were potential as inhibitor of Î±-glucosidase, except for Oscillatoria limnetica and Phormidium sp. isolates. The highest activity in Î±-glucosidase inhibition was detected in Pseudanabaena sp. (14.02%) and Chroococcus sp. (13.0%) isolates.